Aquaculture In Malaysia - Low, Peck Hong (Pusat Pengajian Ilmu Kemanusiaan, 1982)
The aquaculture industry has been receiving increasing attention from the Government of Malaysia. A lot of money had been spent on research. training, subsidies and extension services to develop the industry.